If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -4(2x + -1) + -3x + 2 = 0 Reorder the terms: 9 + -4(-1 + 2x) + -3x + 2 = 0 9 + (-1 * -4 + 2x * -4) + -3x + 2 = 0 9 + (4 + -8x) + -3x + 2 = 0 Reorder the terms: 9 + 4 + 2 + -8x + -3x = 0 Combine like terms: 9 + 4 = 13 13 + 2 + -8x + -3x = 0 Combine like terms: 13 + 2 = 15 15 + -8x + -3x = 0 Combine like terms: -8x + -3x = -11x 15 + -11x = 0 Solving 15 + -11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -11x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -11x = 0 + -15 -11x = 0 + -15 Combine like terms: 0 + -15 = -15 -11x = -15 Divide each side by '-11'. x = 1.363636364 Simplifying x = 1.363636364
| 3x^4-21x^3+24x^2+23x-34=0 | | 20(7u-8v+3w)= | | 7z+2=-6 | | -7+2=6 | | 9x+16-6x=10-2x-19 | | 2p-3=p-5 | | 5a-16=25 | | v^2-10v+16= | | 4w-3x-y-5w+18x-7y= | | -6+[25+(-12)]=43 | | X^2+100+60-3x+30-4x=180 | | -6+[25+(-12)]=31 | | -13+2x=-52+13 | | -6+[25+(-12)]=7 | | -6+[25+(-12)]=19 | | 4=5+2x | | 5x+17-4x=-2-10 | | X/Y=7/11 | | 3x^2-(3m-2)x-(3m+1)=0 | | 1/3*1/3*1/3*1/3*a*a*b*b*c | | 5x-3y=106 | | 16+7yi=8x+i | | x-6=3(2x) | | f-5-3f=7 | | 2x+(x+1)=2 | | 2(4w+9)/4=-10 | | 5x/6-3/2=x/3 | | 0.5(7y+1)-3=8 | | 5(f-1)=25 | | 15m+2n-6m+8n= | | 15x^2+42x=9 | | (1/7)y-4=-18 |